Sovereign Assets and Liabilities Management. (International Monetary Fund, 2000)
This volume, edited by David Folkerts-Landau and Marcel Cassard, consists of papers presented at a conference held in Hong Kong SAR that was hosted by the IMF and the Hong Kong Monetary Authority. It focuses on a wide range of issues confronting policymakers in managing their sovereign assets and liabilities in a world of mobile capital and integrated capital markets. Topics include public debt management strategy, central bank reserves management, technical and quantitive aspects of risk management, and credit costs and borrowing capacity in optimizing debt management. The papers draw on experiences of policymakers and private sector participants actively involved in formulating and implementing debt and reserves policy.